Análise comparativa entre o zoneamento do Plano de Manejo e dos Planos Diretores Municipais na Área de Proteção Ambiental Itupararanga - Moreira, Waldnir Gomes (Universidade Federal de São Carlos, 2025)
Conservation Units are one of the main ways to promote the preservation and sustainable use of natural resources. However, achieving these goals poses several challenges, especially for Environmental Protection Areas (EPAs), a category that can include several anthropic uses, including urban areas. The EPA Itupararanga, located in the southern region of the State of São Paulo, include eight municipalities with different socioeconomic features, and it holds great importance for the preservation of water resources and biodiversity in Alto Sorocaba sub-basin. This study aimed to compare the zoning defined by the Management Plan of this protected area, which establishes regulations, guidelines and restrictions for municipalities within its territory, with the zoning defined by the Municipal Master Plans, the basic instrument of municipal development policy. The zoning overlay was performed using geoprocessing techniques, comparing land use guidelines. Conflicts between the regulatory instruments were identified in more than 50% of EPA’s area, mainly related to the promotion of urban expansion on environmentally fragile and rural areas, which reveals the prevalence of predominant political and economic interests, harming environmental preservation and participatory management. On the other hand, the current Municipal Master Plans mention the EPA and the need to comply with its Management Plan, which was not the case in the previous version, representing a positive step forward to meet its purposes, which highlights the importance of integrated management, with participation of diverse stakeholders. The cartographic data produced will provide tools for the territorial management in the area and support the development of more effective public policies.
Comparative analyses of zoning between management plan and municipal master plans in Environmental Protection Area Itupararanga
Keywords: Unidades de Conservação; Gestão Ambiental; Geoprocessamento; Ordenamento Territorial; Protected Areas; Environmental Management; Geoprocessing; Territorial Ordering; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL::INFORMACAO, CADASTRO E MAPEAMENTO; 6. Água Potável e Saneamento; 11. Cidades e Comunidades Sustentáveis; 12. Consumo e Produção Responsáveis; 14. Vida na Água; 15. Vida Terrestre; 16. Paz, Justiça e Instituições Eficazes